SVD polarization filter taking into account the planarity of ground roll energy - Sánchez-Galvis, Iván-Javier; Serrano-Luna, Jheyston-Omar; Niño-Niño, Carlos-Andrés; Sierra-Bueno, Daniel-Alfonso; Agudelo-Zambrano , William-Mauricio (CT&F - Ciencia, Tecnología y Futuro, 2019)
In real seismic acquisition, the presence of non-planar displacements for surface waves (due for example to scattering) is a common feature. Most polarization filters work on a preferential plane, under the assumption that ground roll displacements can be well represented on a two dimensional projection. In the case of Singular Value Decomposition (SVD), this plane is defined by the two first eigen-images. However, the results we obtained show that in the presence of non-planar energy this assumption does not work properly, and it is necessary to locally decide whether the third SVD value must be included. In this work, planar energy is measured for each time window by a rectilinearity attribute along the second main axis defining a new “planarity criterion” that determines the number of eigen-images that must be filtered. This modified filter was applied to two real 2D3C data sets acquired in Colombia to improve the performance of the ground-roll 3C filtering and was used to characterize the complex particle motion within the ground-roll cone.